Association Between Visual Memory and In Vivo Amyloid and Tau Pathology in Preclinical Autosomal Dominant Alzheimer's Disease. (7th January 2021) - Bocanegra, Yamile; Fox-Fuller, Joshua T.; Baena, Ana; Guzmán-Vélez, Edmarie; Vila-Castelar, Clara; Martínez, Jairo; Torrico-Teave, Heirangi; Lopera, Francisco; Quiroz, Yakeel T.
Abstract: Objective: Visual memory (ViM) declines early in Alzheimer's disease (AD). However, it is unclear whether ViM impairment is evident in the preclinical stage and relates to markers of AD pathology. We examined the relationship between ViM performance and in vivo markers of brain pathology in individuals with autosomal dominant AD (ADAD). Methods: Forty-five cognitively unimpaired individuals from a Colombian kindred with the Presenilin 1 ( PSEN1 ) E280A ADAD mutation (19 carriers and 26 noncarriers) completed the Rey–Osterrieth Complex Figure immediate recall test, a measure of ViM. Cortical amyloid burden and regional tau deposition in the entorhinal cortex (EC) and inferior temporal cortex (IT) were measured using 11 C-Pittsburgh compound B positron emission tomography (PET) and 11 F-flortaucipir PET, respectively. Results: Cognitively unimpaired carriers and noncarriers did not differ on ViM performance. Compared to noncarriers, carriers had higher levels of cortical amyloid and regional tau in both the EC and IT. In cognitively unimpaired carriers, greater cortical amyloid burden, higher levels of regional tau, and greater age were associated with worse ViM performance. Only a moderate correlation between regional tau and ViM performance remained after adjusting for verbal memory scores. None of these correlations were observed in noncarriers. Conclusions: Results suggest that AD pathology and greater age are associated with worse ViM performance in ADAD before the onset of clinical symptoms. Further investigation with larger samples and longitudinal follow-up is needed to examine the utility of ViM measures for identifying individuals at high risk of developing dementia later in life.